Impact of Moringa oleifera Seed-Derived Coagulants Processing Steps on Physicochemical, Residual Organic, and Cytotoxicity Properties of Treated Water - Chales, Geane Garcia [UNESP]; Tihameri, Beatriz Siqueira [UNESP]; Milhan, Noala Vicensoto Moreira [UNESP]; Koga-Ito, Cristiane Yumi [UNESP]; Antunes, Maria Lúcia Pereira [UNESP]; Reis, Adriano Gonçalves Dos [UNESP] (MDPI, 2022)
This study explored the application of whole and defatted Moringa oleifera seed-derived coagulants in powder (P-MOS and DP-MOS), aqueous extraction (AEP-MOS and AEDP-MOS), and saline extraction (SEP-MOS and SEDP-MOS) in the treatment of a synthetic turbid water by coagulation, flocculation, and sedimentation in a jar test apparatus. The performance of M. oleifera seed-derived coagulants was quantified and compared with alum in terms of the ability to neutralize and restabilize the suspension charge, turbidity removal, effect on pH and electrical conductivity, residual organic matter, as well as cytotoxicity in the treated water. All evaluated forms of M. oleifera seed-derived coagulants were able to neutralize and restabilize (in overdose) the particles charges in the suspension. Saline extractions obtained the best turbidity removal results (90%) between the M. oleifera seed-derived coagulants, while alum removed 98% of turbidity. Differently from alum, increased dosage of M. oleifera seed-derived coagulants did not change pH value. Saline extractions and, to a lesser extent, alum increased the electrical conductivity with increasing coagulant dosage. M. oleifera seed-derived coagulants increased residual organic matter (DOC), unlike alum, which did not change this property with increasing dosage. Saline extractions at high dosages enhanced the cytotoxicity to mammalian cells. On the other hand, defatted seeds reduced water cytotoxicity when compared to whole seeds. Despite not being able to reduce the residual organic matter, the previous oil extraction proved to be an important step in the processing of M. oleifera seed-derived coagulants, not changing the turbidity removal capacity and reducing the cytotoxicity of the treated water in addition to generating a significant by-product (Ben oil). Although saline extractions have shown the best turbidity removal results, they should be used with caution due to increased electrical conductivity and cytotoxicity of the treated water at high dosages.
Keywords: coagulation; defatted; dissolved organic carbon; electrical conductivity; extraction; natural coagulants